2016
DOI: 10.26848/rbgf.v9.1.p047-061
|View full text |Cite
|
Sign up to set email alerts
|

Discriminação de Cenários Pluviométricos do Estado da Paraíba Utilizando Distribuição Gama Incompleta e Teste Kolmogorov-Smirnov

Abstract: A incorporação de cenários pluviométricos a estudos de aptidão agrícola é desejável, pois possibilita torná-los ajustados e adequados à variabilidade natural das precipitações e às expectativas pluviométricas dos modelos numéricos de previsão climatológica em uso no Brasil. Devido à importância de conhecer a distribuição das chuvas de uma determinada região, objetiva-se por este trabalho determinar cenários pluviométricos do Estado da Paraíba utilizando o modelo probabilístico distribuição Gama incompleta e o … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
3
0
1
Order By: Relevance
“…of the SST in the tropical Atlantic region due to its proximity to the study area. In the literature, several studies have evaluated precipitation in this region using spatial statistics techniques [7,8]. However, these previous works did not take spatial and temporal dependence into account simultaneously.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…of the SST in the tropical Atlantic region due to its proximity to the study area. In the literature, several studies have evaluated precipitation in this region using spatial statistics techniques [7,8]. However, these previous works did not take spatial and temporal dependence into account simultaneously.…”
Section: Methodsmentioning
confidence: 99%
“…The periodicity is related to the general behavior of sea surface temperature (SST) in the tropical Pacific region, contributing to the events of El Niño and La Niña, and most notably, by the behavior of the SST in the tropical Atlantic region due to its proximity to the study area. In the literature, several studies have evaluated precipitation in this region using spatial statistics techniques [7,8]. However, these previous works did not take spatial and temporal dependence into account simultaneously.…”
Section: Introductionmentioning
confidence: 99%
“…Ao nível de significância de 0,05, (Quadro 1) apenas os dados de reanálise no mesmo período dos dados da estação convencional, seguiram normalidade, sendo assim, foi utilizado o teste de Kolgomorov-Smirnov (K-S), que não necessita da suposição quanto à distribuição do conjunto de dados. O teste K-S é um teste não paramétrico geralmente usado em variáveis aleatórias continuas e serve para comparar as probabilidades empíricas de uma variável com as probabilidades teóricas, estimadas pela função de distribuição em teste (FRACISCO et al, 2016). Esse teste verifica se os valores de uma amostra podem ser considerados como provenientes de uma população com aquela distribuição teórica, e baseia-se no módulo da maior diferença entre a probabilidade observada e a estimada.…”
Section: Análise Estatísticaunclassified
“…Other works carried out by Mossini Junior et al ( 2016) and Passos et al (2017) used the probable monthly and annual rainfall at the levels of 10,20,30,40,50,70,75,80, and 90% using the Gamma probability distribution, having observed that the probable monthly and annual rainfall were achieved with probabilistic levels of 40 to 50%. However, Coan et al (2014);Francisco et al (2015); Francisco et al (2016) worked with the probabilistic model of incomplete Gamma distribution at the levels of 25, 50, and 75% of probability of rainfall.…”
Section: Introductionmentioning
confidence: 99%